Penerapan Metode Pembelajaran Peer Teaching Berbantu Aplikasi Wayground terhadap Hasil Belajar Pendidikan Pancasila Siswa SMKN 1 Perhentian Raja - Afra Mudrikah; Haryono Haryono; Indra Primahardani (Universitas Muhammadiyah Ponorogo, 2026)
Pancasila Education at the Vocational High School (SMK) level still encounters challenges, notably low student achievement driven by the prevalence of conventional instructional methods and a lack of active student participation. This study was conducted to evaluate the impact of implementing a peer teaching method integrated with the Wayground application as an innovative strategy to enhance learning outcomes.Employing a quantitative approach with a quasi-experimental pretest-posttest control group design, the study involved 42 eleventh-grade students from SMKN 1 Perhentian Raja, categorized into experimental and control classes. Learning outcomes were measured using a test instrument previously validated and tested for reliability to ensure data integrity.The findings indicate a significant improvement in learning outcomes within the experimental group compared to the control group. This is evidenced by t-test results, where the thitung > the ttabel at a 0.05 significance level, supported by an N-gain score in the 'moderate' category. Consequently, this study concludes that the Wayground-assisted peer teaching method effectively improves student performance in Pancasila Education and serves as a highly relevant instructional alternative for vocational high schools.